2004
DOI: 10.1089/acm.2004.10.s-49
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promotion Behaviors That Promote Self-Healing

Abstract: A large body of evidence has shown that health-promotion programs in smoking cessation, stress management, fitness, nutrition, weight control, and medical self care have been successful in helping people improve their health practices and related health conditions. However, the impact of these programs on promoting selfhealing among people with acute and chronic diseases is mixed. The purpose of this paper is to identify research opportunities important to fostering a better understanding of health promotion b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 60 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…50 It has been shown that health promotion programs in stress management, fitness, nutrition, weight control, and selfmedication improve health conditions; however, the impact on self-healing among people with acute and chronic diseases has also been shown to be mixed. 51 Self-healing in the context of acute and recurring musculoskeletal pain is the innate process of the body and mind, to promote body networks to return to equilibrium and relieve pain. This may be regulated and optimized by the use of multimodal integrative therapies and refers to a naturally occurring sequence of events, not only of the body but also of the mind.…”
Section: Self-healing Conceptmentioning
confidence: 99%
“…50 It has been shown that health promotion programs in stress management, fitness, nutrition, weight control, and selfmedication improve health conditions; however, the impact on self-healing among people with acute and chronic diseases has also been shown to be mixed. 51 Self-healing in the context of acute and recurring musculoskeletal pain is the innate process of the body and mind, to promote body networks to return to equilibrium and relieve pain. This may be regulated and optimized by the use of multimodal integrative therapies and refers to a naturally occurring sequence of events, not only of the body but also of the mind.…”
Section: Self-healing Conceptmentioning
confidence: 99%